Sintomatologia da depressão e representações sociais de ser idoso e depressão - Oliveira, Marcos Francisco de (2011)
Introduction: The aging, although this is a major victory, is causing a large concern for the rulers, due to the population increase and the risk of illness, capable of affecting the quality of life of older people. Objectives: To evaluate the symptoms of depression referred to by the elderly; knowing the social representations on the elder and depression; and identify psychosocial aspects associated with being elderly and depression. Methodology: an exploratory study, carried out with 240 elderly people in the city of Joao Pessoa-PB. The data were collected by interview semi-structured interviews, Test of Free Association of Words, and Geriatric Depression Scale, were analyzed by software Alceste and SPSS, and interpreted as theoretical social representations. Results: elderly patients presented with age, ranging between 60 and 86 years and more, and most of the patients were female (69.6 % ), married (52.9 % ); Catholics (72.1 % ); can read and write (80.0 % ), with a minimum period of 5 years of schooling (47.5 %) and family income of one to three minimum wages (26.2 % ). Of the 240 elderly people, 75.8 % (182) were classified without degree of symptomatology of depression; 19.6 % (47) manifest light depression, and 4.6 % (11) as severe. From a total of 58 elderly people, with grade depressive mild and severe, it stands out a higher frequency in the age group of 71 to 76 years old (31.0 % ), female (86.0 % ), among the married (41.3 % ), and widowed (34.5 % ), with family income of less than the minimum wage (25.8 % ). Among the 182 elderly people who are not evidenced degree of depression, 154 (84.6 %) can read and write. The data were analyzed by Alceste constituted a corpus of 170 UEC's and four categories of analysis. In the category Meanings Associated With Being Elderly and Depression, suggest that meaningful content focused on negative dimensions, associated with psychosocial aspects such as: abandonment, abuse and bad thoughts. In the category Effects of Aging, the elderly and be silent, incapable, tired, alone and dependent, representing the negative effects of the aging process. In the category Impact to be Elderly and Depression, for the elderly, depression and own the old, mean, disgust, remedy, disgust, disease and ill health, being a stage of life which is in need of good food, work and of himself. In the descriptions on Symptoms of depression and Being an Elder was represented both by the experience of solitude, contempt, anguish, depression, and despair; and by a person of white hair that has peace, experience, accumulation of knowledge, respect and needs to rest. Final Comments: It was found that the older people speak of loneliness, as an experience of the elderly, and the result of the breakdown of the family, with serious social and psychological consequences, which are present in the trajectories of life of the elderly in the study. With respect to the family group, the elderly have untying and/or reduction of family ties, represented by contempt and abandonment, configuring psychosocial aspects more highlighted with the elderly, a fact which may be linked to the isolation or living alone. This way, this situation makes us rethink the different aspects of inequality and trivialization of family values, in particular, the elderly.